Selim vokal kord patolojileri ve tedavi yaklaşımımız - (:unkn) unknown (My University, 1997)
Çalışmamızda Ocak 1987- Nisan İ995 tarihleri arasında selim vokal kord pa¬tolojisi tanısıyla takip ve tedavi edilen 117 hasta incelenmiştir. Tedavi yön¬temi olarak üç Kasta grubu oluşturulmuştur: cerrahi, cerrahi +konuşma te¬rapisi ve sadece konuşma terapisi uygulanan hastalar. Cerrahi yöntemde endolarengeal mikrocerrahi gerçekleştirilmiştir. Vokal nodul ve poliplerin en sık lezyonlar olduğu, cerrahi eksizyon ile konuşma terapisinin tek tek veya kombine edilerek kullanılabileceği görülmüştür.

This study reviewed 117 patients treated for benign pathologies of vocal cords between January 1987 and April 1995. According to treatment mo¬dalities used, the patients were divided into three groups: Patients treated with surgical excision, surgical excision + speech therapy and speech therapy alone, respectively. Surgery was performed using endolaryngeal micro¬surgery. We observed that vocal nodules and polyps were the most frequent benign lesions of the larynx and that surgery and speech therapy were both effective separately or in combination.
Benign vocal cord abnormality and our treatment approach
Keywords: Cerrahi